Archaeology in the Service of the Tribe: Three Episodes in Twenty-first-Century Tribal Archaeology in the US–Mexico Borderlands. Issue 1 (5th November 2015) - Darling, J. Andrew; Lewis, Barnaby V.; Valencia, Robert; Eiselt, B. Sunday
Abstract : The 1987 publication "Uses of the Past: Archaeology in the Service of the State" offers the inspiration for considering the emerging role of descendent communities in archaeological research and cultural resource management in the American Southwest. Recognizing that interpretations of the past are seldom "value neutral", we explore the implications and benefits of interpretations of the past when they are "value tribal". Three episodes in twenty-first-century Tribal Archaeology in Arizona are considered including repatriation of religious objects under state statutes, international repatriation of human remains, and Tribal documentation of traditional cultural properties. We conclude that as federally recognized tribes initiate their own programs in archaeological investigation and assume greater responsibility in the cultural resource management process, new perspectives on the past are coming to light that are of potential benefit to everyone.